Visit of the Soviet Union journalists' delegation to Finland and the Baltic countries in 1937: the report of the leader of the delegation, Boris Michailov, to Stalin and Molotov - Zenonas Butkus; Magnus llmjärv (Lietuvos Istorijos Studijos)
The article presents the leader's of the USSR journalists' delegation, Michailov's, report to Stalin and Molotov on the July 19-August 10, 1937 visit to Finland, Estonia, Latvia, and Lithuania, which was found in the Russian State Archive for Social and Political History, Molotov's Stock (f. 82, i. 2, r. 1020, p. 4-16). The document presented might seem to be complete propaganda, bloated with class struggle, and in general full of Marxist clichés. It is, however, an authentic testimony of the attitude formed by those in the highest circles of Soviet authorities towards the Baltic countries. The attitude became of high importance to those countries' fate in just a few years. Soviet clichés notwithstanding, the document also reflects the internal and international situation of the countries. The visit itself was not just an ordinary fact of cultural ties but an action motivated by international political considerations, which has not been addressed in historical works yet.